Forest and Land Fire Management Strategy in South Sumatra Province through the Penta Helix Model - Febri Haryadi; Sena Putra Prabu Jaya; Andy AlFatih (Publikasi Indonesia, 2024)
Aiming to find out the Forest and Land Fire Management Strategy in South Sumatera Province through the Penta Helix Model, the strategy parameters according to Geoff Mulgan are measured using 5 indicators, namely: Purposes, Environment, Direction, Action, and Learning, the author concludes that the Forest and Land Fire Management Strategy in South Sumaetra Province through the Penta Helix Model has not been successful. This is due to several things as follows: 1) actions to overcome forest and land fires have not been optimal, resulting in forest and land fires continuing to occur; 2) human activities that still clear land by burning; 3) weather conditions or the dry season and even forest and land fire incidents increase during the El Nino phenomenon; 4) community participation in preventing forest and land fires is not yet optimal.